The role of virus infection in a virus-evolutionary genetic algorithm - Kubota, Naoyuki; Shimojima, Koji; Fukuda, Toshio (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with a genetic algorithm based on virus theory of evolution (VEGA). The VEGA realizes horizontal propagation and vertical inheritance of genetic information in a population with virus infection operators and genetic operators. The main operator of the VEGA is a reverse transcription one, which plays the role of a crossover and a selection simultaneously.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka